Dietary components and risk of cardiovascular disease and all-cause mortality: a review of evidence from meta-analyses. (September 2019) - Kwok, Chun Shing; Gulati, Martha; Michos, Erin D; Potts, Jessica; Wu, Pensee; Watson, Lorraine; Loke, Yoon K; Mallen, Christian; Mamas, Mamas A
Aims: The optimal diet for cardiovascular health is controversial. The aim of this review is to summarize the highest level of evidence and rank the risk associated with each individual component of diet within its food group. Methods and results: A systematic search of PudMed was performed to identify the highest level of evidence available from systematic reviews or meta-analyses that evaluated different dietary components and their associated risk of all-cause mortality and cardiovascular disease. A total of 16 reviews were included for dietary food item and all-cause mortality and 17 reviews for cardiovascular disease. Carbohydrates were associated with a reduced risk of all-cause mortality (whole grain bread: relative risk (RR) 0.85, 95% confidence interval (CI) 0.82–0.89; breakfast cereal: RR 0.88, 95% CI 0.83–0.92; oats/oatmeal: RR 0.88, 95% CI 0.83–0.92). Fish consumption was associated with a small benefit (RR 0.98, 95% CI 0.97–1.00) and processed meat appeared to be harmful (RR 1.25, 95% CI 1.07–1.45). Root vegetables (RR 0.76, 95% CI 0.66–0.88), green leafy vegetables/salad (RR 0.78, 95% CI 0.71–0.86), cooked vegetables (RR 0.89, 95% CI 0.80–0.99) and cruciferous vegetables (RR 0.90, 95% CI 0.85–0.95) were associated with reductions in all-cause mortality. Increased mortality was associated with the consumption of tinned fruit (RR 1.14, 95% CI 1.07–1.21). Nuts were associated with a reduced risk of mortality in a dose–response relationship (all nuts: RR 0.78, 95% CI 0.72–0.84; tree nuts: RR 0.82, 95% CI 0.75–0.90; and peanuts: RR 0.77, 95% CI 0.69–0.86). For cardiovascular disease, similar associations for benefit were observed for carbohydrates, nuts and fish, but red meat and processed meat were associated with harm. Conclusions: Many dietary components appear to be beneficial for cardiovascular disease and mortality, including grains, fish, nuts and vegetables, but processed meat and tinned fruit appear to be harmful.